VACCINATION OF CALVES WITH LIVE MODIFIED AND LIVE VIRULENT STRAIN OF SALMONELLA TYPHIMURIUM - Habasha, F G (The Iraqi Journal of Veterinary Medicine, 1996)
Sixteen normal colostrum-fed -Friesian and Holestein-Friesian X Angus crossbred calves, ranging in age from 2 to 7 weeks were divided into 4 vaccinated groups and 1 nonvaccinated (control) group. Group I consisted of 2 calves vaccinated orally twice at a two week interval with small doses of organisms ( 104 thar1l05 live virulent Salmonella gghimurium, strain 108-11). Group ll consisted of 2 calves vaccinated orally twice at two weeks interval with 1011 organisms (modified Salmonella typhimurium, strain SL 3261 ). Group [[1 consisted of 2 calves vaccinatedlivitwice at two weeks interval with small doses of organisms ( 104 than 105 virulent Salmonella typhimurigg, strain 108-11). Group IV consisted of 3 calves which were vaccinated 1M twice atv/o weeks interval with109 live modiﬁed strain 108-11(SL 1479). Group V consisted of 7 calves which served as nonvaccinated controls. One to two weeks after the final vaccine close all calves were orally challenge exposedwith 1.5x 1011 viable Salmonella typliimurium, strain 108-11. The results of vaccination with different preparation of vaccine indicated that a modiﬁed live vaccine strain designated as SL 1479 with complete, nonreverting blocks in aromatic biosynthesis may beappropriate for protecting domestic animals against Salmonella infection.